Tissue sulfomucin and sialomucin content in colon mucosa without intestinal transit subjected to intervention with Curcuma longa (curcumin) - Alves Júnior,Antonio José Tiburcio (2017)
Abstract Purpose: To measure the tissue sulfomucin and sialomucin content of the colon mucosa without fecal flow, subjected to intervention with curcumin, and the influence of the concentration used and the intervention time. Methods: Thirty-six rats were subjected to proximal right colostomy and distal mucous fistula. They were divided into two groups according to whether sacrifice was performed two or four weeks after the intervention. Each group was divided into three subgroups according to the enema applied daily: saline alone; curcumin at 50 mg/kg/day or curcumin at 200 mg/kg/day. Acid mucins were diagnosed using the Alcian blue technique. The mucin content was quantified by means of computer-assisted image analysis. The significance level of 5% was used throughout (p < 0.05). Results: There were dose-related increases in the quantities of sulfomucins in the animals subjected to interventions with curcumin, both after two weeks (p < 0.00001) and after four weeks (p < 0.00001). There were increases in sialomucin quantity that were concentration-related (p < 0.00001) and time-related (p < 0.00001). Conclusion: Curcumin enemas increase the quantity of acid mucins in the intestinal flow in the excluded colon, with dose and time dependency.